2001
DOI: 10.1021/om0101994
|View full text |Cite
|
Sign up to set email alerts
|

Role of Halide Ions in Divalent Palladium-Mediated Reactions:  Competition between β-Heteroatom Elimination and β-Hydride Elimination of a Carbon−Palladium Bond

Abstract: The integral role of halide ions as a ligand in the reactions of stoichiometric arylpalladium reagents and Pd(II)-catalyzed reaction of phenylmercuric acetate with various allylic compounds were studied. The halide ion was found to inhibit β-H elimination and promote β-heteroatom elimination in acidic media. In this reaction, a C-Pd intermediate with a β-heteroatom (including halogen, acetoxy, alkoxy, and hydroxyl groups) gives only β-heteroatom elimination product in the presence of halide ions, while β-H eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…These allenes were formed by carbopalladation and subsequent b-hydroxy elimination. Such a b-heteroatom elimination is not a favored process [16] compared with the b-Scheme 2. Design of our system and anticipated sequence to intercept the formal anti-carbopalladation intermediate 4.…”
mentioning
confidence: 97%
“…These allenes were formed by carbopalladation and subsequent b-hydroxy elimination. Such a b-heteroatom elimination is not a favored process [16] compared with the b-Scheme 2. Design of our system and anticipated sequence to intercept the formal anti-carbopalladation intermediate 4.…”
mentioning
confidence: 97%
“…Our previous work has shown that excess of halide ions can block the usual b-hydride elimination [21,40]. In the above catalytic cycle, the normal b-hydride elimination is also inhibited and b-acetoxy elimination takes place from the alkylpalladium intermediate III (scheme 9).…”
Section: Role Of Nitrogen-containing Ligandsmentioning
confidence: 94%
“…Catalytic reactions. Then, we turned our attention to Pd(II)-initiated reaction in which the carbon-palladium bond was quenched with b-heteroatom elimination (scheme 1) [40]. In the synthesis of a-haloalkylidene-b-vinyl-c-butyrolactone derivatives from the enyne-coupling of 4¢-halo-2¢-alkenyl alkynoates, excess halide salts were used to obtain high (Z)-stereoselectivity of the exocyclic double bond in the lactone products [15,16].…”
Section: Halopalladation-olefin Insertion-b-heteroatommentioning
confidence: 99%
See 2 more Smart Citations